PEMANFAATAN MEDIA AUDIO VISUAL DALAM MENUMBUHKAN MOTIVASI BELAJAR ANAK TK ISLAM HARAPAN INDAH PONTIANAK - Yunita, Rita; Syukri, M; Ali, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThis study aims to describe the use of audio visual media in growing children's learning motivation at Harapan Indah Islamic Kindergarten in West Pontianak Subdistrict. This study uses descriptive methods and uses a qualitative approach. The source of this research data is the class teacher and the accompanying teacher group B1 to B6, totaling 11 people and children from groups B1 to B6. The results of research into the use of audio visual media in fostering learning motivation are that children have a learning spirit, learning discipline, learning responsibility, and learning success. The way the teacher enhances the spirit of children's learning is that the teacher creates a class environment that is fun for children so that the children when they are in the classroom feel calm. The way teachers grow children's discipline in learning is by displaying films that teach children how to discipline. The teacher's way of fostering children's learning responsibilities is to invite children to watch movies, but the films that show are more directed towards Islam. The way the teacher fosters the seriousness of the child in learning is by making the media full of colors and images so that the children can focus on the future of the child. The learning motivation of children after using audio visual media is that children feel happy in learning so that children show an attitude of enthusiasm, discipline, responsibility and serious learning. Keywords: Audio Visual Media, Children?s Learning Motivation